Rhetorical criticism: theory, Application and critics - Cardozo Mindiola, Cristian (Corporación Universitaria Americana, 2018)
Resumen El presente arti?culo busca describir el enfoque hermene?utico conocido como “criticismo retorico”, analizar sus presuposiciones, aplicar el enfoque a la carta de Filemo?n y por ultimo ofrecer una cri?tica del enfoque. Este estudio muestra que el criticismo retorico resulta ser una herramienta u?til para la hermene?utica literaria ya que en reaccio?n a los movimientos que colocan el significado del texto en la comunidad que lo crea, el criticismo retorico busca determinar las intenciones del autor y los elementos que e?l uso? para hacer persuasivo su discurso. Palabras Clave: Reto?rica, Filemo?n, Hermene?utica, Biblia, Historia. Abstract This article seeks to describe the hermeneutical approach known as "rhetorical criticism", analyze its presuppositions, apply the approach to the letter of Philemon and finally offer a critique of the approach. This study shows that rhetorical criticism turns out to be a useful tool for literary hermeneutics since in reaction to the movements that place the meaning of the text in the community that creates it, the rhetorical criticism seeks to determine the intentions of the author and the elements that he used to make his speech persuasive. Keywords: Rhetoric, Philemon, Hermeneutics, Bible, History.